Jiawei Suanzaoren decoction for the treatment of perimenopausal insomnia: clinical observation and experimental study - Chen, Li-Qiong; Zhou, Yong-Can; Ning, Fang; Zhu, Ming-Jin (Frontiers in Pharmacology, 2025)
BackgroundTraditional Chinese medicine has a good clinical therapeutic effect on perimenopausal insomnia, Jiawei Suanzaoren Tang (JW-SZRT) has a significant therapeutic effect on people with yin deficiency and fire excess type insomnia.MethodFirstly, 80 cases of perimenopausal yin deficiency and fire excess type insomnia were included in the study. The treatment group was treated with Jiawei Suanzaoren decoction, while the control group was treated with lorazepam for 4 weeks. The study observed and compared the Pittsburgh Sleep Quality Index (PSQI), Kupperman score, Polysomnography (PSG) and sex hormone levels of two groups before and after treatment. Secondly, we also conducted network pharmacology analysis and mechanism research. We first searched public databases for the targets of the compound known tobe associated with JW-SZRT, as well as those predicted to be targets of insomnia, and then used software Cytoscape 3.7.2, GO and KEGG to identify enriched gene pathways and networks. Networks and pathways that overlapped between Insomnia-associated proteins and JW-SZRT target proteins were then used to predict candidate protein targets of JW-SZRT in insomnia. Finally, 40 rats were selected in animal experimentation and 30 perimenopausal insomnia rat models were created through ovariectomy and a modified multi-platform water environment 72-hour sleep deprivation method. The model group received normal saline, the western medicine group received lorazepam suspension, and the Chinese medicine group received Jiawei Suanzaoren decoction. The sham surgery group was given routine feeding. The sleep condition, the levels of blood hormone levels and the expression levels of 5-Hydroxytryptamine (5-HT) and Gamma-Aminobutyric Acid receptor A (GABAA) receptor in the hypothalamus were compared between groups.ResultsIn clinical observation, the sleep condition and the changes of hormone levels between the treatment group and the control group were statistically significant (P < 0.05). The results of network pharmacology indicate that in the main signaling pathways for treating insomnia, it is speculated that Jiawei Suanzaoren Tang can regulate the signaling pathway of neuroactive ligand receptor interactions by inhibiting the activation of related proteins, thereby improving sleep. Animal experiments have also shown that the JW-SZRT can significantly improve the sleep conditions of insomnia rats during perimenopause, and the expression levels of 5-HT and GABAA receptors in the hypothalamus had a significant difference between groups in animal experiments (P < 0.05).ConclusionJiawei Suanzaoren Decoction can improve the perimenopausal insomnia. The mechanism behind this improvement may be related to the regulation of Estradiol (E2), Follicle-Stimulating Hormone (FSH), and luteinizing hormone (LH) levels, as well as the mRNA expression levels of 5-HT1a, 5-HT2a, GABAARα1, and GABAARγ2 receptors in the hypothalamus.